A multidisciplinary evaluation of suspected, non-confirmed cases of COVID-19 including chest CT, as compared to World Health Organization recommendations. Issue 5 (May 2021) - McGrath, J.; Kenny, C.; Smyth, H.; McGinty, T.; Sheehan, G.; Gaine, S.; McCullagh, B.; MacMahon, P.; Egan, J.J.; Cotter, A.
Abstract : AIM: To report an audit of the evaluation of suspected, unconfirmed cases of COVID-19 including chest computed tomography (CT), as compared to World Health Organization recommendations. METHODS: A clinical audit was undertaken examining the evaluation of patients with suspected COVID-19 with negative SARS-CoV-2 reverse transcriptase polymerase chain reaction (RT-PCR) results, with comparison to WHO recommendations. A retrospective chart review was undertaken for 90 patients examining investigations, in particular CT, used to clarify the diagnosis. RESULTS: Ninety patients underwent additional investigation. Seventy-five per cent adherence to WHO recommendations was observed. Fifty-two men (57.78%) and 38 (42.22%) women were investigated, with a median age of 69 years (range 20–96 years). Seventy-nine chest CT examinations demonstrated positive, indeterminate, and negative rates for COVID-19 of 3.79%, 24.1%, and 72.15% respectively. Three patients had discordant swab results with initially negative and subsequently positive results for SARS-CoV-2, resulting in false-negative rates of 5.1% for those retested. Combining discordant RT-PCR swab results, positive radiology, and patients treated as COVID-19-positive due to indeterminate radiology and highly consistent symptoms, resulted in a false-negative rate for initial SARS-CoV-2 RT-PCR swabs of 16.67%. CONCLUSION: Seventy-five per cent compliance with relevant WHO guidance and a false-negative rate for initial swabs of 16.67% was demonstrated. Further evidence is needed to fully determine the utility of chest CT in the diagnosis of COVID-19 in the context of initial false-negative RT-PCR results. Highlights: Positive CT findings for COVID-19 seen in 3.7% of patients with initial negative swab. Indeterminate CT findings for COVID-19 seen in 24.1% of patients with negative swabs. Negative CT findings for COVID-19 seen in 72.15% of patients with negative swabs. Discordant COVID-19 swab result seen in 5% of patients with initial negative results.